Penerapan Algoritma Backtracking Dan Metode Constraint Satisfaction Untuk Penjadwalan Matakuliah - FERDINAL R (DEPATI PARBO PRESS, 2018)
ABSTRACT School activity scheduling in a college is complex matter. Besides seen from space side, time, also must be seen from lecturer side, that is lecturer possibility teach more than one existing subject in school, because there subject in school total possibility and ill assorted lecturer total, so that must be thought also solution so that lecturer not teach two subject in school differ on and clock same. Besides, must considering also class availability so that activity learn enforceable. The one of method that can be used to finish troubleshoot by using approach method constraint satisfaction problem and algorithm backtracking. Constraint satisfaction problem used to find conditon or object that fulfil amount of rules and criteria. Algorithm backtracking to be one of algorithm solution in solution livelihood better from another algorithm. this algorithm looks for problem solution without investigate all existing possibilities, but only solution possibility up at considering. supposed with be used it algorithm backtracking be got optimal scheduling that is where happen best combination for subject in school pair and teacher lecturer as a whole, there is no time-table quarrel troubleshoot in student university side, with space availability enough and appropriate according to facilities to entire existing subject in school. Keyword : algorithm backtracking, constraint satisfaction problem, scheduling, data base, ERD, heuristic search